2016
DOI: 10.1007/s12550-016-0241-2
|View full text |Cite
|
Sign up to set email alerts
|

Urinary deoxynivalenol (DON) and zearalenone (ZEA) as biomarkers of DON and ZEA exposure of pigs

Abstract: Four diets contaminated with 1.1 to 5.0 mg/kg deoxynivalenol (DON) and 0.4 to 2.4 mg/kg zearalenone (ZEA) were fed to four groups of six growing Large White pigs. Urine samples were collected after 3 to 4 days and again after 6 to 7 days on the diets. On each sampling day, half of the animals were sampled in the morning, after an 8-h fast, and the other half were sampled in the afternoon, after 7 h of ad libitum access to feed. The urinary concentrations of DON, DON-glucuronide, DON-3-sulphate, de-epoxy-DON, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…The optimized MRM parameters are shown in Table 1 . The result showed that DON, NIV, and ZEA exhibited higher response in ESI negative mode while 3AcDON/15AcDON, F-X, and T-2 toxin exhibited higher response in ESI positive mode, consistent with previous literature [ 38 , 39 , 40 ].…”
Section: Resultssupporting
confidence: 90%
“…The optimized MRM parameters are shown in Table 1 . The result showed that DON, NIV, and ZEA exhibited higher response in ESI negative mode while 3AcDON/15AcDON, F-X, and T-2 toxin exhibited higher response in ESI positive mode, consistent with previous literature [ 38 , 39 , 40 ].…”
Section: Resultssupporting
confidence: 90%
“…Urine samples were diluted to the same creatinine content with water in order to obtain similar concentrations of matrix compounds in all samples [ 23 ]. Apparent recoveries varied between 84% (β-ZEL) and 113% (α-ZEL-GlcA).…”
Section: Resultsmentioning
confidence: 99%
“…Since the discrepancy existed in the absorption, metabolism and clearance procedures, the tolerance for the toxicity and pathogenic dose of DON were different for different animal species in vivo [ 19 , 20 ]. DON was degraded by microorganisms into a variety of products (such as de-epoxy-DON) in the digestive tract or in the intestinal mucosa, liver, kidney, and other organs.…”
Section: Discussionmentioning
confidence: 99%